Hepatic branch vagus nerve plays a critical role in the recovery of post-ischemic glucose intolerance and mediates a neuroprotective effect by hypothalamic orexin-A. - Shinichi Harada; Yui Yamazaki; Shuichi Koda; Shogo Tokuyama (PLoS ONE)
Orexin-A (a neuropeptide in the hypothalamus) plays an important role in many physiological functions, including the regulation of glucose metabolism. We have previously found that the development of post-ischemic glucose intolerance is one of the triggers of ischemic neuronal damage, which is suppressed by hypothalamic orexin-A. Other reports have shown that the communication system between brain and peripheral tissues through the autonomic nervous system (sympathetic, parasympathetic and vagus nerve) is important for maintaining glucose and energy metabolism. The aim of this study was to determine the involvement of the hepatic vagus nerve on hypothalamic orexin-A-mediated suppression of post-ischemic glucose intolerance development and ischemic neuronal damage. Male ddY mice were subjected to middle cerebral artery occlusion (MCAO) for 2 h. Intrahypothalamic orexin-A (5 pmol/mouse) administration significantly suppressed the development of post-ischemic glucose intolerance and neuronal damage on day 1 and 3, respectively after MCAO. MCAO-induced decrease of hepatic insulin receptors and increase of hepatic gluconeogenic enzymes on day 1 after was reversed to control levels by orexin-A. This effect was reversed by intramedullary administration of the orexin-1 receptor antagonist, SB334867, or hepatic vagotomy. In the medulla oblongata, orexin-A induced the co-localization of cholin acetyltransferase (cholinergic neuronal marker used for the vagus nerve) with orexin-1 receptor and c-Fos (activated neural cells marker). These results suggest that the hepatic branch vagus nerve projecting from the medulla oblongata plays an important role in the recovery of post-ischemic glucose intolerance and mediates a neuroprotective effect by hypothalamic orexin-A.